ADAPTASI DAN ANTISIPASI PETANI SERTA STRATEGI PENERAPAN SISTEM USAHATANI DALAM MENGATASI FENOMENA PERUBAHAN IKLIM DI PROVINSI NUSA TENGGARA TIMUR - Iqbal, Muhammad; Nurasa, Tjetjep (Lampung University)
This article is aimed to analyze the farmerâs adaptation, anticipation, and farming system implementation strategy towards mitigation of climate change phenomenon in East Nusa Tenggara (NTT) Province. The adaptation, anticipation, and strategy of farming system implementation at farmer level should be developed in order to mitigate the climate change phenomenon in NTT. It is caused by their natural experience and indiggenous konowledge. Based on locally internal and external potencies and constraints, therefore, five priority programs can be formulated to anticipate the climate change phenomenon mitigation. There are : (1) introducing corn variety that tolerates drought; (2) implementing climate farmerâs field school for agricultural extension workers and farmerâs groups; (3) improving dryland cropping pattern; (4) constructing the small-scale reservoir at farmer level; and (5) conducting farmerâs training on corn post harvest technologies such as drying, peeling, packaging, and storage. These programs should be implemented through collaborative participation among farmers, governmental agencies, private sectors, non-governmental organizations, and other related institutions.Â